HPV33+ HNSCC is associated with poor prognosis and has unique genomic and immunologic landscapes. (January 2020) - Chatfield-Reed, Kate; Gui, Shanying; O'Neill, Wendi Q.; Teknos, Theodoros N.; Pan, Quintin
Highlights: HPV33+ HNSCC has a worse overall survival compare to HPV16+ HNSCC. The APOBEC associated mutation signature was higher in HPV16+ than HPV33+ HNSCC. Aneuploidy was higher in HPV33+ HNSCC than in HPV16+ HNSCC. CD8 T-cell infiltration was reduced in HPV33+ compared to HPV16+ tumors. Abstract: Objective: To determine the influence of high-risk HPV genotype on outcomes in HNSCC patients. Materials and Methods: This is a retrospective analysis of The Cancer Genome Atlas HNSCC cohort. Results: Using multivariate Cox regression analysis, we revealed that HPV33+ HNSCC patients have inferior overall survival compared to HPV16+ HNSCC patients independent of anatomical site (HR 3.59, 95% CI 1.58–8.12; p = 0.002). A host anti-viral immune response, apolipoprotein B mRNA editing enzyme, and catalytic polypeptide-like mutational signature, was under represented and, aneuploidy and 3p loss were more frequent in HPV33+ tumors. A deconvolution RNA-Seq algorithm to infer immune cell fractions revealed that CD8+ cytotoxic T-cell infiltration was reduced in HPV33+ compared to HPV16+ tumors (1.3% vs. 2.7%, p = 0.007). TGFB1, a negative modulator of T-cell infiltration and function, showed expression and pathway enrichment in HPV33+ tumors. Conclusions: Our work reveals that HPV genotype, in particular HPV33, has a powerful impact on HNSCC patient survival. We argue that p16 immunohistochemistry as a surrogate biomarker for HPV+ status will lead to sub-optimal risk stratification and advocate HPV genotype testing as standard of care.